MANAGEMENT OF THE SUBJECT TEACHER FORUM (MGMP) FOR CULTURAL ARTS - Ika Rahayu Susanti; Rojiah; Yeti Herawati; Maman Herman; Dede Iman (Program Studi Manajemen Pendidikan Islam, 2026)
This study is grounded in the critical importance of effective management of the Cultural Arts Subject Teacher Forum (MGMP) in enhancing the professional competence of junior high school teachers, particularly within the context of implementing the Merdeka Curriculum. Despite its strategic role, empirical studies that comprehensively link MGMP management processes with measurable outputs, outcomes, and impacts remain limited. Therefore, this study aims to analyze the management of the Cultural Arts MGMP in the Majenang Regional Commission, Cilacap Regency, focusing on process, output, outcome, and impact dimensions in improving teachers’ professional competence and the quality of instruction. This study employed a descriptive method with a qualitative approach, utilizing a case study design. The research subjects included MGMP administrators, Cultural Arts teachers, school principals, and supervisors. Data were collected through in-depth interviews, participant observation, and document analysis. The data analysis followed the interactive model of Miles and Huberman, involving data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation of techniques, sources, and time. The findings reveal that: (1) MGMP management has been implemented systematically through needs-based planning, structured organization, collaborative implementation, and continuous evaluation and follow-up; (2) the outputs of the MGMP include instructional materials, artistic works, and improvements in teachers’ practical skills that are both applicable and collaborative in nature; (3) the outcomes indicate an enhancement in teachers’ professional competence, particularly in planning, implementing, and evaluating Cultural Arts instruction; and (4) the impact is reflected in the improved quality of teaching and learning, as evidenced by increased student engagement and improved learning outcomes. In conclusion, the Cultural Arts MGMP functions as an effective professional learning community that significantly contributes to enhancing both teacher competence and instructional quality.